Assaying the Antiplatelet Ticagrelor by Validated UV Spectrophotometric Method with Performance Equivalent to HPLC - Sales Oliveira, Sendy; da Silva Bitencourt, Andressa; Gobetti, Caren; Sebastian Loureiro Mendez, Andreas; Virginia Garcia, Cassia (Current Pharmaceutical Analysis, 2017)
Objective: An analytical assay with focus on UV spectrophotometric method was proposed as alternative for the analysis of the antiplatelet ticagrelor. Method: Method performance was continuously evaluated, establishing limits for reported parameters that denote reproducibility during routine analysis. By selecting solvent and extractive system, the validation parameters were well executed based on experimental protocols that were exhaustively tested. Results: Preliminary tests indicated an adequate UV profile using methanol and applying ultrasonic bath as mechanical support to extract ticagrelor from tablets matrix. The extractive solution was compared to placebo solution following the same sample preparation, in order to evaluate eventual interference from matrix excipients and affirming the method's specificity. Linearity assay at 255 nm showed a good capacity on drug estimation in the range of 7.5 - 30.0 µg/mL (r = 0.9996). In parallel, quantitation was applied with focus on precision and accuracy, whose results indicated good response on data reproducibility (RSD intraday=1.60-1.84%; RSD interday=0.39) and potential to determine the drug in spiked matrix (% of standard recovery=101.90; RSD< 2.0%). The known robustness profile for spectrophotometric assay was confirmed, demonstrating reliability on drug quantitation after small variations in solvent brand, equipment and λ (nm) (% drug content=100.78-104.44%). Conclusion: By statistical comparison to HPLC, the validated spectrophotometric assay can be used alternatively for ticagrelor determination on routine analysis.
Keywords: Ticagrelor